Effects of pore size, implantation time, and nano‐surface properties on rat skin ingrowth into percutaneous porous titanium implants. Issue 5 (7th June 2013) - Farrell, Brad J.; Prilutsky, Boris I.; Ritter, Jana M.; Kelley, Sean; Popat, Ketul; Pitkin, Mark
<x xml:space="preserve">Abstract</x> The main problem of percutaneous osseointegrated implants is poor skin‐implant integration, which may cause infection. This study investigated the effects of pore size (Small, 40–100 μm and Large, 100–160 μm), nanotubular surface treatment (Nano), and duration of implantation (3 and 6 weeks) on skin ingrowth into porous titanium. Each implant type was percutaneously inserted in the back of 35 rats randomly assigned to seven groups. Implant extrusion rate was measured weekly and skin ingrowth into implants was determined histologically after harvesting implants. It was found that all three types of implants demonstrated skin tissue ingrowth of over 30% (at week 3) and 50% (at weeks 4–6) of total implant porous area under the skin; longer implantation resulted in greater skin ingrowth (p < 0.05). Only one case of infection was observed (infection rate 2.9%). Small and Nano groups showed the same implant extrusion rate which was lower than the Large group rate (0.06 ± 0.01 vs. 0.16 ± 0.02 cm/week; p < 0.05). Ingrowth area was comparable in the Small, Large, and Nano implants. However, qualitatively, the Nano implants showed greatest cellular inhabitation within first 3 weeks. We concluded that percutaneous porous titanium implants allow for skin integration with the potential for a safe seal. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 1305–1315, 2014.